Analisis Kolaborasi Hubungan Karyawan Menggunakan Metode Social Network Analysis (Studi Kasus Dinas Kearsipan dan Perpustakaan Kabupaten Boyolali) - Kuncoro, Wreda Agung; Sediyono, Eko; Hartomo, Kristoko Dwi (Jurnal Transformatika, 2023)
Good local government performance, especially related to the realization of good corporate governance, can be created if there is good communication between agencies, employees and compact collaboration to synergize policies that facilitate public services. To optimize government performance, one of which is the Boyolali District Archives and Library Service through collaborative relationships between employees so as to create intense two-way communication. This study aims to identify social networks related to collaboration between employees using the Social Network Analysis method and a total of 40 people as respondents, but only 32 people filled out the questionnaire data completely. The indicators used in viewing the research results are density values, degree centrality values, closeness centrality values, betweenness centrality values, and clique values. The results of the analysis obtained a network density level of 14.8% (considered weak because it is less than 50 percent). Employee number 21 has the highest degree centrality value and betweenness centrality value, then employee number 9 has the highest closeness centrality. This research concludes that there is a good collaborative relationship between the four departments in the Archives and Library Office of Boyolali Regency, namely the Operations department, the Service department, the Archives department, and the Librarian department.